Thermal modeling of deep borehole heat exchangers for geothermal applications in densely populated urban areas - Morchio, Stefano; Fossa, Marco (Thermal science and engineering progress, 2019)
•A detailed analysis of deep borehole for geothermal heat pumps application is presented.•The method is applied to study the behavior of coaxial pipes to be employed in densely populated urban areas.•Validation is performed to assess model accuracy and reliability, offering contributions to previous papers on the subject. Ground coupled heat pumps are known as very energy efficient heating and cooling systems for a variety of building applications. In densely populated areas where new urbanization is intense, deep ground heat exchangers can be a valuable and effective solution for geothermal heat pump applications. In this paper a finite difference numerical model has been developed starting from literature contributions by Holmberg et al. (2016). The in house Fortran90 code has been built and validated to cope with variable longitudinal and radial mesh distribution for simulating coaxial pipe configurations. Different ground properties and geothermal gradients can be applied. Far field boundary conditions, ground pipe meshing and Courant numbers have been varied for enhancing the accuracy in predicting the fluid temperature evolution. The model has been extensively validated against analytical solutions and literature data. The model has been applied for analyzing the behavior of deep heat exchangers in the 500–800 m range and the effects of the pipe diameter ratio have been investigated both in terms of fluid temperature evolution and pressure losses inside inner and annular pipes.